Consumptive water usage of evaporative pads - C. Schmidt; John F. Smith; Joseph P. Harner; Michael J. Brouk (Kansas Agricultural Experiment Station Research Reports, 2006)
Consumptive water usage by evaporative pads was measured during 7 days of a 3-week period at a Kansas (KS) dairy and a 2-day pe-riod at a North Dakota (ND) dairy. Water me-ters were installed between the water hydrants, and evaporative pads at each dairy, and were monitored. Data were recorded every 30 min-utes during 5 hr at the KS site and every 15 minutes during 1 to 2.5 hr at the ND site. Ra-tio of pad area to cow equaled 4.8 and 4.5 ft2 per cow at the KS and ND sites, respectively. Airflow rates through the pads were 1.2, 2.1, and 3.2 mph at the ND dairy and 3.3 mph at the KS dairy. During the study period in KS, the temperature humidity index ranged from 78 to 86 and water usage varied from 0.7 to 4.7 gallon per minute. Average pad efficiency equaled 62%. Water usage averaged 0.3 gal-lons per hr per ft2 of pad when airflow rate was 3.3 to 3.6 mph. At the ND dairy, the wa-ter usage averaged 0.1, 0.3, and 0.38 gallon per hr per ft2 of pad for the low, medium, and high airflow rates, respectively. The tempera-ture humidity index equaled 65, 72.5, and 71 for the low, medium, and high airflow study periods. Pad efficiency averaged 93, 86, and 81% from the low to high airflow rates. Simi-lar to pad efficiencies at the KS site, efficiency increased as the outdoor air temperature de-creased. (Key Words: Cooling; Dairy Day, 2006, Kansas State University, Manhattan, KS, 2006;
Keywords: Dairy Day; 2006; Kansas Agricultural Experiment Station contribution; no. 07-118-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 965; Dairy; Cooling systems; Evaporative cooling; Water usage